MANIPULATING THE PITCH SIZE CONSTRAINS THE PLAYERS’ POSITIONING DURING UNBALANCED SOCCER SMALL-SIDED GAMES PLAYED BY DIFFERENT AGE GROUPS (Kinesiology, 2022)
We aim to investigate the impact of variable soccer pitch sizes on the position of players during unbalanced small-sided games (SSGs) and compare the responses of players from two different age groups. Forty-eight young players (n = 24 under-13 and n = 24 under-14) took part in the study and played 3 vs. 3 + 1 SSGs on two different pitch sizes (smaller: 36 x 27 m / 139m2 per player; and larger: 40 x 29 m / 166 m2 per player). Players’ positions on the pitch (length, width, length-to-width ratio, stretching index, and spatial exploration index) were assessed by the positional data provided by global position system devices and were compared within age groups and between game formats using a two-way analysis of variance. Results showed higher values of spatial exploration index (SEI) in the larger SSGs than in the smaller format (p